Note: Answers should have no zero or negative exponents.
1) -24x^2y^3 - 30x^5 y + 6xy^2 / 6xy^2
2) 2[-3A - 2(2B + 4A) + B]
2) $\displaystyle -2[-3A - 2(2B + 4A) + B] = -2(-3A - 4B - 8A + B)$
$\displaystyle = -2(-11A - 3B)$
$\displaystyle = 22A + 6B$
$\displaystyle = 2(11A + 3B)$.
1) I can't tell if your original expression is
$\displaystyle -24x^2y^3 - 30x^5y + \frac{6xy^2}{6xy^2}$
or
$\displaystyle \frac{-24x^2y^3 - 30x^5y + 6xy^2}{6xy^2}$.
Please either use brackets correctly, or use LaTeX.
LaTeX is the programming language used for mathematical typesetting - i.e. what I used to post my responses...
$\displaystyle \frac{-24x^2y^3 - 30x^5y + 6xy^2}{6xy^2} = \frac{6xy(-4xy^2 - 5x^5 + y)}{6xy^2}$
$\displaystyle = \frac{-4xy^2 - 5x^5 + y}{y}$
$\displaystyle = -4xy - \frac{5x^5}{y} + 1$.